The beat cop Chicago's Chief O'Neill and the creation of Irish music - O'Malley, Michael (The University of Chicago Press, 2022)
"Francis O'Neill was Chicago's larger-than-life police chief, starting in 1901- and he was an Irish immigrant with an intense interest in his home country's music. In documenting and publishing his understanding of Irish musical folkways, O'Neill became the foremost shaper of what "Irish music" meant. He favored specific rural forms and styles, and as Michael O'Malley shows, he was the "beat cop" -actively using his police powers and skills to acquire knowledge about Irish music and to enforce a nostalgic vision of it"--
Keywords: O'Neill, Francis -- 1848-1936; Irish / Illinois / Chicago / Music / History and criticism; Folk music / Illinois / Chicago / History and criticism; Folk music / Ireland / History and criticism; O'Neill, Francis / 1848-1936; Police chiefs / Illinois / Chicago / Biography; Irish / Illinois / Chicago / Social life and customs; National characteristics, Irish; Irlandais / Illinois / Chicago / Musique / Histoire et critique; Musique folklorique / Irlande / Histoire et critique; Chefs de police / Illinois / Chicago / Biographies; Irlandais / Illinois / Chicago / Murs et coutumes; Irlandais; Folk music; Irish / Music; Irish / Social life and customs; Police chiefs; Illinois / Chicago; Ireland; Biography; Biographies; Criticism, interpretation, etc; Biografie